MiR-409-3p Inhibits Cell Proliferation and Invasion of Osteosarcoma by Targeting Zinc-Finger E-Box-Binding Homeobox-1 - Wu, Liang; Zhang, Yiming; Huang, Zhongyue; Gu, Huijie; Zhou, Kaifeng; Yin, Xiaofan; Xu, Jun (Frontiers in Pharmacology, 2019)
Background: Osteosarcoma (OS) takes the lead as bone cancer in the world. Reports are evidencing the involvement of MicroRNA-409 (miR-409-3p) in causing tumor and its development. However, its possible role in causing OS needs more clarification. Methods: we, therefore, designed the present study, to determine the expression level, its clinical significance, and mode of action of miR-409-3p in OS. Results: By this study we found that miR-409-3p level was diminished in cell lines and OS tissues compared with associated adjacent non-tumorous tissues and a non-cancer osteoblastic cell line, respectively. Low miR-409-3p expression level was linked with clinical stage and distant metastasis of OS cases. Resumption expression of miR-409-3p attenuated cell proliferation and invasion in OS. Additionally, based on Bio-informatic analysis, we predicted that Zinc-finger E-box-binding Homeobox-1 (ZEB1) is a possible target gene of miR-409-3p. It was further confirmed with luciferase reporter assay, RT-qPCR and Western blot analysis. Conclusion: In the findings of the current study we observed up-regulation of ZEBI in OS tissue cases, and this up-regulation was inversely proportional to the miR-409-3p expression level. Furthermore, down-regulation of ZEB1 decreased OS cell invasion and proliferation, illustrating that the tumor suppressive roles of miR-409-3p in OS cells may be exerted via negative regulation of ZEB1. Taken together, our observations highlight the potential role of miR-409-3p as a tumor suppressor in OS by partial down-regulation of ZEB1 and suggest a potential application of miR-409-3p in OS treatment.